Controlling DC permeability in cast steels - Sumner, Aaran; Gerada, Chris; Brown, Neil; Clare, Adam (Elsevier, 2017)
Annealing (at multiple cooling rates) and quenching (with tempering) was performed on specimens of cast steel of varying composition. The aim was to devise a method for selecting the steel with the highest permeability, from any given range of steels, and then increasing the permeability by heat treatment. Metallographic samples were imaged using optical microscopy to show the effect of the applied heat treatments on the microstructure. Commonly cast steels can have DC permeability altered by the careful selection of a heat treatment. Increases of up to 381% were achieved by annealing using a cooling rate of 6.0 °C/min. Annealing was found to cause the carbon present in the steel to migrate from grain boundaries and from within ferrite crystals into adjacent pearlite crystals. The migration of the carbon resulted in less carbon at grain boundaries and within ferrite crystals reducing the number of pinning sites between magnetic domains. This gives rise to a higher permeability. Quenching then tempering was found to cause the formation of small ferrite crystals with the carbon content of the steel predominately held in the martensitic crystal structures. The results show that with any given range of steel compositions the highest baseline DC permeability will be found with the steel that has the highest iron content and the lowest carbon content. For the samples tested in this paper a cooling rate of 4.5 °C/min resulted in the relative permeability of the sample with the highest baseline permeability, AS4, increasing from 783 to 1479 at 0.5 T. This paper shows how heat treatments commonly applied to hypoeutectoid cast steels, to improve their mechanical performance, can be used to also enhance electromagnetic properties of these alloys. The use of cast steels allows the creation of DC components for electrical machines not possible by the widely used method of stacking of electrical grade sheet steels.